ANALYSIS OF ADAPTIF LOCAL REGION IMPLEMENTATION ON LOCAL THRESHOLDING METHOD - I Gusti Agung Socrates Adi Guna; Hendra Maulana; Agus Zainal Arifin; Dini Adni Navastara (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2016)
Thresholding is a simple and effective technique for image segmentation. Thresholding techniques can begrouped into two categories, global thresholding and local thresholding. All local threshold method generallybegins with determining thresholds in each pixel by checking the area centered on the pixel, using a box shape (x,y) which is fixed by the size of the neighborhood